PENGARUH KINERJA KEUANGAN PERBANKAN SYARIAH TERHADAP BAGI HASIL DEPOSITO MUDHARABAH PADA BANK KALBAR SYARIAH CABANG SAMBAS PERIODE 2019-2021 - Wahyuni, Sri; Marina; Purnamasari, Wulan (Cross-Border Journal of Business Management, 2025)
ABSTRACT This study aims to examine the effect of the level of profitability, level of financing, and level of efficiency on the level of profit sharing for mudharabah deposits. The level of profitability is proxied by return on assets (ROA), financing is proxied by the financing to deposit ratio (FDR), and the level of efficiency is proxied by Operating Costs to Operating Income (BOPO). While the dependent variable used in this study is the rate of profit sharing for mudharabah deposits. This study uses secondary data using published data on financial statements at Bank Kalbar Syariah Sambas Branch for the 2019-2021 period. The analytical method used is multiple linear regression, and before performing the regression test, the classical assumption test is first performed. The results of this study indicate that Operational Costs on Operating Income (BOPO), return on assets (ROA) and financing to deposit ratio (FDR) partially have a positive and significant effect on the rate of profit sharing on mudharabah deposits at Bank Kalbar Syariah Sambas Branch for the 2019-2021 period. . Simultaneously, Operational Costs on Operating Income (BOPO), return on assets (ROA) and financing to deposit ratio (FDR) together have a positive and significant impact on the rate of profit sharing on mudharabah deposits at Bank Kalbar Syariah Sambas Branch for the 2019-2021.